Penentuan Rasio BOD/COD optimal pada reaktor Aerob, Fakultatif dan Anaerob - Arifani Rakhma Putri (Jurnal Teknik Lingkungan, 2013)
ABSTRACTThere are a variety of wastewater substances both organic and non-organic. The content of the wastewater can be harmful to living things when directly discharged into river or water bodies. Organic substances are safe for the environment is the end result in the wastewater treatment. BOD and COD are simple and important parameters for checking the content of organic matter. The BOD / COD ratio  is an indicator of the impact of organic matter so that the required for the output of the wastewater treatment. The purpose of this study is to determine the BOD / COD ratio optimal in a good treatment for aerobic, facultative and anaerobic process by artificial Glucose monohydrate-Glacial Acetic Acid with batch reactor. The BOD / COD ratio optimum obtained in each process is the aerobic process that is at ratio of 0.1, the ratio of the facultative and anaerobic processes are at ratio 0.2 . But the most optimal among all the views from the best efficiency is the ratio of aerobic BOD / COD initial 0.1. The study is expected to be a reference because this study is a preliminary study with laboratory scale so that the need for further research to provide more optimal.